Editorial: How to develop a quality research article and avoid a journal desk rejection. (February 2022) - Dwivedi, Yogesh K.; Hughes, Laurie; Cheung, Christy M.K.; Conboy, Kieran; Duan, Yanqing; Dubey, Rameshwar; Janssen, Marijn; Jones, Paul; Sigala, Marianna; Viglia, Giampaolo
Abstract: The desk rejection of submitted articles can be a hugely frustrating and demotivating process from the perspective of the researcher, but equally, a time-consuming and vital step in the process for the Editor, tasked with selecting appropriate articles that meet the required criteria for further review and scrutiny. The feedback from journal Editors within this editorial, highlights the significant gaps in understanding from many academics of the journal assessment process and acceptance criteria for progression to the review stage. This editorial offers a valuable "lived-in" perspective on the desk rejection process through the lens of the Editor, via the differing views of nine leading journal Editors. Each Editor articulates their own perspectives on the many reasons for desk rejection, offering key insight to researchers on how to align their submissions to the specific journal requirements and required quality criteria, whilst demonstrating relevance and contribution to theory and practice. This editorial develops a succinct summary of the key findings from the differing Editor perspectives, offering a timely contribution of significant value and benefit to academics and industry researchers alike.